Age Differences in the Use of Health Information Technology Among Adults in the United States: An Analysis of the Health Information National Trends Survey. (January 2021) - Onyeaka, Henry K.; Romero, Perla; Healy, Brian C.; Celano, Christopher M.
Background: Despite significant advancements in the use of health information technologies (HITs) in health care, older adults' adoption of new technologies has consistently lagged behind that of younger adults.Objective: To compare ownership rates and preferences for utilizing technology for health information exchange among older and younger adults.Methods: Utilizing data from the 2017 and 2018 iterations of the Health Information National Trends Survey ( n = 6789), we performed multivariable logistic regression while controlling for sociodemographic characteristics.Results: Older adults were less likely than younger adults to own technological devices such as smartphones, less likely to report finding these tools beneficial in monitoring their health, and less likely to use these tools in communicating with their health providers. However, these differences were substantially attenuated after adjustment for technology ownership.Discussion: Future research should aim to identify factors associated with access, usability, and adoption of HIT for managing care among older adults.